Founding mothers women in America in the Revolutionary era - De Pauw, Linda Grant; McCurdy, Michael (Boston Houghton Mifflin, 1975)
Describes the daily lives, social roles, and contributions of women living during the revolutionary period.
Keywords: Women -- History -- United States -- Juvenile literature; Women -- History; Women -- Social conditions; Women -- Social conditions -- United States -- Juvenile literature; Women's rights -- History. -- United States; United States -- Social life and customs -- To 1775 -- Juvenile literature; United States -- Social life and customs -- To 1775.